IDENTIFIKASI PROBLEMATIKA YANG DIHADAPI GURU DALAM PEMBELAJARAN BIOLOGI - murtini, iin (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2023)
Purpose: To find out what problems or obstacles occur in the biology learning process. Design/methodology/approach: The type of research is qualitative description with observation methods. Data was collected through distributing questionnaires to science (Natural Science) subject teachers at MTS Mansaul Huda Bonjor Sarang and SMPN 1 Bancar. Findings: The problems of teachers at MTS Mansaul Huda Bonjor and SMPN 1 Bancar are similar, namely the lack of laboratory facilities that support practical work.Many teachers experience problems in learning, including biology learning. The research examines the problems experienced by teachers in teaching biology. The aim of the research is to find out what problems or obstacles occur in the biology learning process. The research method used is qualitative description with data collection based on sampling by distributing questionnaires to science subject teachers at MTS Mansaul Huda Bonjor Sarang and SMPN 1 Bancar. The results of this research conclude that the problems of teachers at MTS Mansaul Huda Bonjor and SMPN 1 Bancar are similar, namely the lack of laboratory facilities that support practicums. The learning process carried out so far at MTS MANsal Huda Bonjor is still not effective and students are still relatively passive, whereas at SMPN 1 Bancar the learning looks active. MTS Mansaul Huda Bonjor teachers are honorary teachers whose welfare is lacking, while SMPN 1 Bancar teachers are on average PNS (Civil Servants) whose welfare is more guaranteed.